Electrically switchable, Ka-band slotted waveguide antenna array system - Sekretarov, S.S.; Vavriv, D.M.; Volkov, V.A.; Natarov, M.P.; Glamazdin, V.V. (Electrically switchable, ka-band slotted waveguide antenna array system / S.S. Sekretarov, D.M. Vavriv, V.A. Volkov, M.P. Natarov, V.V. Glamazdin // Радіофізика та електроніка. — 2008. — Т. 13, № 3. — С. 489-493. — Бібліогр.: 4 назв. — англ., 2008)
An original electrically switchable, Ka-band slotted waveguide antenna array system has been recently developed, produced, and tested. The system consists of four identical sections, which are connected to a radar transmitter/receiver by means of a high-power, multipole p-i-n switch. The introduced p-i-n switch enables for a fast electrical scanning of the antenna beam what essentially extends possible areas of the antenna system application. The antenna system is used in a helicopter collision avoidance, surveillance, and weather radar. This paper describes design features of the antenna system, its main characteristics, results of its testing, and the antenna integration in the radar.